Efektivitas Sistem E-Filing Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Pemahaman Internet Sebagai Variabel Moderasi Pada Tax Center UIN Sayyid Ali Rahmatullah Tulungagung - Eva Alfiatin; Faizal Satria Desitama (Jurnal Akuntansi dan Pajak, 2023)
This study discusses the Effectiveness of the E-Filing System on Individual Taxpayer Compliance with Internet Understanding as a Moderation Variable at the UIN Sayyid Ali Rahmatullah Tulungagung Tax Center. The implementation of the e-filing system can be seen from the urgency of implementing e-filing, the purpose of holding e-filing, whether it has been achieved, socialization with the implementation of e-filing and the constraints that exist if there is an implementation of e-filing, when the Tax Center can continue to improve services such as increasing the number of tax volunteers in assisting taxpayers in reporting Annual SPT or conducting socialization related to the application of the e-filing system and the impact of individual taxpayers not reporting Annual SPT so that the e-filing system can be said to be effective in its application. The results of this study indicate that (1) The effectiveness of the E-Filing System has a positive and significant effect on Individual Taxpayer Compliance. This is evidenced by simple linear regression. The analysis obtained shows an R Square value of 0.314. (2) Understanding the Internet cannot moderate (strengthen) the Effectiveness of the E-Filing System on the Compliance of Individual Taxpayers who report their Annual SPT at the UIN Sayyid Ali Rahmatullah Tulungagung Tax Center. This is because many taxpayers who understand or do not understand the application of the e-filing system continue to report their Annual SPT using the e-filing system with assistance from filling in by tax volunteers, relatives, and KPP Primary employees. Therefore, taxpayers who do not understand will still not understand the application of the e-filing system. Keywords: e-filing system, taxpayer compliance, internet.